The values of bureaucracy - Du Gay, Paul. (Oxford : Oxford University Press, 2005)
"This book describes and analyzes the impact of contemporary programmes of organizational reform in the public and private sectors on bureaucratic structures. It aims to show how and why bureaucratic forms of organization have a vital role in ordering our political, social, economic, and cultural existence"--Provided by publisher.
part 1. The politics of bureaucracy -- part 2. The end of bureaucracy and public management -- part 3. Bureaucracy and public management -- part 4. Bureaucracy and civil society.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Palo Alto, Calif. : ebrary, 2014. Available via World Wide Web. Access may be limited to ebrary affiliated libraries.
Keywords: Bureaucracy; Organizational change; Electronic books